The Role and Potential Therapeutic Application of Myeloid-Derived Suppressor Cells in Allo- and Autoimmunity - Qi Zhang; Masayuki Fujino; Jinhua Xu; Xiao-kang Li (Mediators of Inflammation)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells that consists of myeloid progenitor cells and immature myeloid cells. They have been identified as a cell population that may affect the activation of CD4+ and CD8+ T-cells to regulate the immune response negatively, which makes them attractive targets for the treatment of transplantation and autoimmune diseases. Several studies have suggested the potential suppressive effect of MDSCs on allo- and autoimmune responses. Conversely, MDSCs have also been found at various stages of differentiation, accumulating during pathological situations, not only during tumor development but also in a variety of inflammatory immune responses, bone marrow transplantation, and some autoimmune diseases. These findings appear to be contradictory. In this review, we summarize the roles of MDSCs in different transplantation and autoimmune diseases models as well as the potential to target these cells for therapeutic benefit.